2016
DOI: 10.3389/fpsyg.2016.00564
|View full text |Cite
|
Sign up to set email alerts
|

Event-Related Potentials and Emotion Processing in Child Psychopathology

Abstract: In recent years there has been increasing interest in the neural mechanisms underlying altered emotional processes in children and adolescents with psychopathology. This review provides a brief overview of the most up-to-date findings in the field of event-related potentials (ERPs) to facial and vocal emotional expressions in the most common child psychopathological conditions. In regards to externalizing behavior (i.e., ADHD, CD), ERP studies show enhanced early components to anger, reflecting enhanced sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 82 publications
1
7
0
Order By: Relevance
“…In Experiment 2 we investigated the ability to recognize emotions from facial expressions and its modulation by gaze direction in ASD and TD children by means of the emotion composite task. The observed overall lower performance of the ASD group as compared to TD children might reflect a global deficit in categorizing facial expressions as reported in many other studies ( Wong et al, 2008 ; Chronaki, 2016 ). However, since we had no non-emotional control task, it might also reflect a more general phenomenon in the ASD group, e.g., task compliance related differences between the groups.…”
Section: Methodssupporting
confidence: 66%
See 1 more Smart Citation
“…In Experiment 2 we investigated the ability to recognize emotions from facial expressions and its modulation by gaze direction in ASD and TD children by means of the emotion composite task. The observed overall lower performance of the ASD group as compared to TD children might reflect a global deficit in categorizing facial expressions as reported in many other studies ( Wong et al, 2008 ; Chronaki, 2016 ). However, since we had no non-emotional control task, it might also reflect a more general phenomenon in the ASD group, e.g., task compliance related differences between the groups.…”
Section: Methodssupporting
confidence: 66%
“…Event-related potential (ERP) studies indicate difficulties of individuals with ASD in orienting to social stimuli. This was demonstrated by a reduced or delayed N170 response to faces, which may indicate impaired structural processing of faces ( Samaey et al, 2020 ) or diminished emotion recognition ( Chronaki, 2016 ). The N170 is one of the most frequently investigated face-sensitive ERP components, and is also associated with eye gaze processing ( Pelphrey et al, 2005 ; Senju et al, 2005b ; Webb et al, 2006 ).…”
Section: Introductionmentioning
confidence: 99%
“…Second, power tends to be enhanced in the left (LH) relative to the right hemisphere (RH) across frequency bands in ASD (relative to controls) (Cantor et al ., ; Stroganova et al ., ). With reference to ERPs, longer latencies and reduced amplitudes during facial emotion processing have been observed in ASD for the P100 (Chronaki, ), N170 (McPartland et al ., ; Dawson et al ., ,b) and the P300 (Dawson et al ., ,b; Chronaki, ). By way of linking these themes to this study, prior research points to posterior parietal and temporoparietal regions with reference to such spectral power differences and ERP components relevant to social cognition (Itier & Taylor, ; McCleery et al ., ; Mavratzakis et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Impaired recognition of emotions can be caused by problems in orienting to emotional stimuli. An eye tracking study (Ahmadi, Judi, Khorrami, Mahmoudi-Gharaei, & Tehrani-Doost, 2011) and few Event-Related Potential (ERP) studies reported that these impairments are associated with early stages of facial emotion processing and selective attention in ADHD (Williams et al, 2008; Barry et al, 2009; Nazari et al, 2010; Sarraf Razavi, Tehranidoost, Ghassemi, Purabassi, & Taymourtash, 2017), as well as autism spectrum disorders Chronaki (2016). In addition, ERP studies reported deficits in selective attention in other cognitive tasks in ADHD (Barry et al, 2009; Nazari et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Literature reporting the neural basis of emotional dysfunction in children with ADHD is scarce. To our knowledge and according to a review article by Chronaki (2016), the current study is the first to investigate the early stages of neural activity of facial emotion recognition based on EPN component in children with ADHD. The present study aimed to better understand the early stages of facial emotion processing in children with ADHD.…”
Section: Introductionmentioning
confidence: 99%